Gest??o estrat??gica de pessoas e comprometimento em organiza????es hospitalares: um estudo multicasos - Silva, Claudio Cesar da (2014)
This research came from the interest that, in recent years, the strategic management of people and organizational commitment are reaching in contemporary organizations, being the most researched topics in their respective areas. However, there has been a reduced number of qualitative studies on these subjects, able to provide greater depth to the data collected and observed. In this sense, this research has been characterized by qualitative, exploratory, based on multiple case studies in hospital organizations. Its contribution, among others, resided in understanding how the strategic management of people may favor the organizational commitment, having as subject the managers of hospital organizations, and in the expansion of the discussions that are already being conducted in the field of study of organizational commitment on the need to ensure a greater conceptual precision to the concept of organizational commitment. To achieve this goal, established themselves as specific objectives: analyze the congruence between the institutional strategic planning and the planning of personnel management; identify the policy and practice of strategic management of people which can contribute to organizational commitment; Learn about the concepts and perceptions about organizational commitment, assigned by the managers and; relate the concepts of organizational commitment of managers, with the definition (s) thus submitted by the literature. The data were collected through in-depth interviews with key managers, application of survey experience with intermediate managers and documentary research. For the treatment of the data and the analysis of the results content analysis techniques, reflective analysis, document analysis and, as a result, the triangulation of data were used. Their results showed that: When the policy and practice of strategic management of people are integrated with organizational strategies, There is a trend in the area of personnel management in acting directed to the model of commitment; the policies and practices of recruitment and selection, training, development and education, working conditions, skills and performance evaluation and rewards, are perceived by the managers of hospital organizations as contributory to the commitment; the central aspects of concepts and perceptions about organizational commitment, prepared by managers, highlighted the commitment, the dedication and the identification with the Organization, What are characteristics of the affective dimension of commitment, no references to normative and instrumental dimensions were observed.